2020
DOI: 10.4292/wjgpt.v11.i3.59
|View full text |Cite
|
Sign up to set email alerts
|

Tongue thickness in health vs cirrhosis of the liver: Prospective observational study

Abstract: BACKGROUND Malnutrition affects 40%-90% of patients with cirrhosis of the liver. L3 skeletal muscle index (L3SMI) is presently accepted as the most objective and quantitative measure available for sarcopenia, a surrogate marker of malnutrition. L3SMI application is, however, limited by non-availability of computed tomography scanning in remote areas, cost, need for extensive training, and the risk of exposure to radiation. Therefore, an alternative dependable measure with wider availability is nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Methods to assess muscle mass in patients with cirrhosis are detailed in Table 3. [171][172][173][174][175][176][177][178] CT imaging is currently the gold standard for assessment of muscle mass in cirrhosis, but cost and exposure to ionizing radiation make routine use of CT solely for the purpose of detecting sarcopenia impractical in many clinical settings. (129) However, when abdominal CT imaging is performed for clinical reasons-such as in patients with HCC or for surgical planning (e.g., transplant, hepatectomy)-muscle mass measurement can be obtained from clinical scans using readily available quantitative morphomics software.…”
Section: Sarcopenia Assessment Of Sarcopenia In Adults and Childrenmentioning
confidence: 99%
“…Methods to assess muscle mass in patients with cirrhosis are detailed in Table 3. [171][172][173][174][175][176][177][178] CT imaging is currently the gold standard for assessment of muscle mass in cirrhosis, but cost and exposure to ionizing radiation make routine use of CT solely for the purpose of detecting sarcopenia impractical in many clinical settings. (129) However, when abdominal CT imaging is performed for clinical reasons-such as in patients with HCC or for surgical planning (e.g., transplant, hepatectomy)-muscle mass measurement can be obtained from clinical scans using readily available quantitative morphomics software.…”
Section: Sarcopenia Assessment Of Sarcopenia In Adults and Childrenmentioning
confidence: 99%
“…To explain the path from liver function to characteristics of SV, the concept of "liver tongue" has long appeared in TCM, and it is considered to be a specific manifestation of liver cirrhosis 41 . A study recommended that the measurement of tongue thickness should be considered for diagnosing sarcopenia in cirrhosis of the liver 42 . Another study found that patients with liver cirrhosis are more likely to develop sublingual varices 43 , specifically swelling and extreme fullness of the SV.…”
Section: Discussionmentioning
confidence: 99%
“…SV sublingual veins, SV-L the value of the sublingual veins on the L-axis in Lab colour space, SV-a the value of the sublingual veins on the a-axis in Lab colour space, SV-b the value of the sublingual veins on the b-axis in Lab colour space, T1 grade 1 of sublingual veins tortuosity, T2 grade 2 of sublingual veins tortuosity, T3 grade 3 of sublingual veins tortuosity, L1 grade 1 of sublingual veins trunk-length, L2 grade 2 of sublingual veins trunk-length, L3 grade 3 of sublingual veins trunk-length, W1 grade 1 of sublingual veins width, W2 grade 2 of sublingual veins width, W3 grade 3 of sublingual veins width. www.nature.com/scientificreports/ measurement of tongue thickness should be considered for diagnosing sarcopenia in cirrhosis of the liver 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Measurements of the tongue muscle thickness in the group of patients with liver cirrhosis showed an association with the CHILD and MELD score, and a distinctive difference between the group of healthy control group, but with no proven CT control correlation. The definition of liver cirrhosis in the article was relatively loose[ 41 ].…”
Section: Diagnostic Methods In the Field Of Sarcopeniamentioning
confidence: 99%